Uji Organoleptik Selai Buah Buni - I Putu Juma Diva Wirya Gitama; Desak Gede Candra Widayanthi (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2020)
This study aimed to analyze the quality of jam with the basic ingredients of buni fruit through organoleptic tests. The collection in the process of making buni jam included organoleptic tests through panelist assessments by filling out Likert scale questionnaires. Organoleptic tests were carried out based on 4 variables, namely smell, taste, color, and texture. As a result of the research, buni jam is considered to have excellent quality in terms of smell, taste, texture, and color. For this reason, buni jam is considered to be an alternative to buni fruit processing to increase its economic value. As a follow-up to this research, it is recommended to carry out further research to examine the cost, the level of durability/storability of the jam, and the nutritional value of the jam. This can be a significant input in the formulation of a comprehensive strategy in buni fruit processing.